DIALOG SEBAGAI UPAYA MENEPIS PANDANGAN NEGATIF ATAS KERAGAMAN AGAMA - Anis Tilawati; Nur Kafid (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2015)
The diversity of religion and believe in the world broughtout various model of interaction. The result of those process ofinteraction could be positive of negative perpestives. From the positiveperspective would bring out the attitude of tolerance, even just in thescope of social-life. Whereas the negative perspective would emergewhen among religious believers have not aware about the diversities ofbelief. Furthermore, from this perspective then emerge conflict andviolence which is used and religion as its justification. Basically, everyproblem have its solution, including the case/conflict which is usingthe name of religion. And dialogue as one of the problem solving to beused to skim or overcome the negative perspective about the religiousdiversities.